Anodal tDCS Over the Right Temporoparietal Junction Lowers Overbidding in Contests - Wang, Minda; Li, Jianbiao; Li, Dahui; Zhu, Chengkang (Frontiers in Neuroscience, 2019)
Overbidding, which means bidding over the Nash equilibrium, is commonly observed in a competitive social interaction, such as a contest or auction. Recent neuroscience data show that the rTPJ is related to overbidding and associated with inferring the intentions of others during competitive interactions. The present study investigates the neural underpinning of overbidding and tests how the rTPJ may impact bidding behavior by using tDCS to modulate activation of the rTPJ. Participants completed a two-person proportional prize contest, in which overbidding was frequently observed and each participant’s share of the prize was equal to the individual expenditure divided by aggregated expenditures. We observed a significant tDCS effect in that participants’ average expenditure and overbidding rates were significantly reduced in anodal stimulation compared with cathodal and sham stimulation. Possible explanations include that enhanced activity in the rTPJ via anodal stimulation increased participants’ accuracy in inferring the strategies of others, or participants’ concern for others, and thus could help them to bid optimally. Our findings provide evidence supporting that activation of the rTPJ in contest could affect overbidding and bidding strategy and further confirm previous studies, which suggest that in a competition context, the rTPJ is involved in the inference of mental states.